Association between hypertension and the severity of new onset ischemic stroke in Diabetic patients - Sina, Hashmi; Mustary, Tamanna; Ahmed, Kazi Gias Uddin; Chowdhury, Ahmed Hossain; Saha, Kanol; Arifuzzaman, Mohammad; Siddique, Abu Raihan; Alam, lftikher; Dhali, Sabbir Ahmed; Ahmed, Sharif Uddin (Journal of Dhaka Medical College, 2020)
Objective: To evaluate the association between hypertension and the severity of new onset ischemic stroke patient with diabetes mellitus. Method: This Cross sectional study was carried out in the Department of Neurology, BSMMU, Dhaka, from February 2013 to September 2014 on 50 patients with first attack of ischemic stroke with DM. mRS was measured on 14th day of the stroke. During this period other important relevant investigations were also recorded. Result: In this study, out of 50 patients, 40.0% were in age group 51-60 years and the mean age of the patients was 58.9 ± 9.6 years with a range from 30 to 75 years. Males were 52.0% and females were 48.0%. Male to female ratio was 1.08:1. It was observed that more than one third (36.0%) patients were current smoker, 9(18.0%) were former smoker and 23(46.0%) were non smoker. More than half of the patients had hypertension (58.0%). Mean systolic BP was 129 ±16 mmHg with a range from 90 to 160 mmHg and the mean diastolic BP was 81±11 mmHg with a range from 60 to 100 mmHg. No association was found between hypertension with severity of new onset ischemic stroke in Diabetic patients. Conclusion: As per study result it can be concluded that there is no association between hypertension and the severity of new onset ischemic stroke in Diabetic patients. J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 7-10